A randomized clinical trial of motivational interviewing plus skills training vs. Relaxation plus education and 12-Steps for substance using incarcerated youth: Effects on alcohol, marijuana and crimes of aggression. (1st February 2020) - Stein, L.A.R.; Martin, Rosemarie; Clair-Michaud, Mary; Lebeau, Rebecca; Hurlbut, Warren; Kahler, Christopher W.; Monti, Peter M.; Rohsenow, Damaris
Highlights: Compared to MI/CBT, RT/SET useful in reducing alcohol use in youth after release. Both RT/SET and MI/CBT reduced predatory aggression. Compared to MI/CBT, RT/SET helpful in reducing alcohol-related predatory aggression. Abstract: Background: Motivational Interviewing plus Cognitive Behavior Therapy (MI/CBT) has been used to reduce adolescent substance use, but has rarely been applied in youth correctional settings. This trial compared MI/CBT against Relaxation Training plus Substance-Education/12-Steps (RT/SET) to reduce substance use and crime among incarcerated youth. Methods: Participants ( N = 199) were incarcerated juveniles (64.8 % non-White, 10.1 % girls, mean age of 17.1 years). Two individual sessions of MI (or RT) were followed by 10 group sessions of CBT (or SET). Youth were randomized to condition with follow-ups at 3- and 6-months after release. Major outcomes included alcohol, marijuana and crimes involving aggression. Results: A marginal treatment by time interaction was found for percent heavy drinking days, with follow-up tests indicating less alcohol use in RT/SET than MI/CBT at 6 months, and increased use within MI/CBT from 3 to 6 months. A significant treatment by time interaction was found for alcohol-related predatory aggression, with follow-up tests indicating fewer youth engaged in this behavior from 3 to 6 months within RT/SET, and weak evidence favoring MI/CBT over RT/SET at 3 months. General predatory aggression decreased from 3 to 6-months for both treatments. Conclusions: Although weak evidence was found favoring MI/CBT with respect to alcohol-related predatory aggression, results generally support RT/SET in reducing percent heavy drinking days.